Մաշկեւորի վանական միաբանութիւնը եւ ձեռագրական ժառանգութիւնը (ԺԲ.—ԺԴ. դդ.) - Բադալեան, Հասմիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена истории монастыря Машкевор, одного из региональных духовно-культурных центров Киликийской Армении XII—XIV веков, деятельности монастырских писцов, членов и служителей конгрегации и оценке наследия скриптория. Данная статья является первым полным исследованием и основана на рукописных источниках Матенадарана имени Маштоца, каталогах армянских рукописей, а также результатах историко-филологических исследований. Впервые изучены и представлены одиннадцать рукописей из Машкеворского монастыря, а также выявлены имена писцов и обстоятельства копирования рукописей. The article is dedicated to the history of the Mashkevor Monastery, one of the regional spiritual and cultural centers of Cilician Armenia between the 12th—14th centuries. This article discusses activities of monastic scribes and members of the congregation, circumstances of copying manuscripts, and the assessment of the scriptorium heritage. The research is based on the manuscript sources of Matenadaran named after Mashtots, catalogues of Armenian manuscripts from around the world, as well as the results of historical and philological research. For the first time, eleven manuscripts from the Mashkevor Monastery have been studied and brought to scholars’ attention.
Keywords: Պատմաբանասիրություն